Comprehensive immunophenotypic study of acute myeloid leukemia with KMT2A (MLL) rearrangement in adults: A single‐institution experience. Issue 2 (28th December 2021) - Konoplev, Sergej; Wang, Xiaoqiong; Tang, Guilin; Li, Shaoying; Wang, Wei; Xu, Jie; Pierce, Sherry A.; Jia, Fuli; Jorgensen, Jeffrey L.; Ravandi, Farhad; Issa, Ghayas C.; Medeiros, L. Jeffrey; et al.
Abstract: Background: Acute myeloid leukemia (AML) with KMT2A ( MLL ) rearrangement is known for monocytic or myelomonocytic differentiation, but the full immunophenotypic spectrum and dynamic changes of the immunophenotype in this genetically defined disease have not been systematically studied. Methods: We reviewed the immunophenotype, karyotype, and mutations at the time of initial diagnosis and relapse of adults with AML with KMT2A rearrangement in our institution between 2007 and 2020. Results: We identified 102 patients: 44 men and 58 women with a median age of 52 years (range, 18–87). Forty‐three patients were considered to be therapy‐related. Twenty‐four out of 64 patients relapsed from complete remission after induction therapy, 34 had persistent/progressive disease, and 58 patients died with a median overall survival of 17 months. We detected five immunophenotypes: immature monocytic (38%); myelomonocytic (22%); myeloblastic (22%); mature monocytic (10%); and acute promyelocytic (APL)‐like (8%). By chromosomal breakpoints, we presumed 11 different partners; t(9;11) (p22;q23)/ MLLT3‐KMT2A was the most common rearrangement ( n  = 56, 55%), followed by t(6;11) (q27;q23)/ AFDN‐KMT2A ( n  = 13, 13%). Patients with t(6;11) (q27;q23)/ AFDN‐KMT2A preferentially showed a myeloblastic phenotype ( p  = 0.026). Mutations were detected in 39/64 (61%) cases, and RAS pathway ( NRAS/KRAS/PTPN11 ) was involved in 26/64 (41%) cases. None of the APL‐like cases had mutations detected. At the time of disease relapse, 10/24 (42%) showed major immunophenotypic change, and 7/10 cases gained additional cytogenetic and/or molecular alterations. Conclusion: The immunophenotype of AML with KMT2A rearrangement is more diverse than previously recognized, with a substantial subset showing no evidence of monocytic differentiation. Major immunophenotype change is common at the time of relapse.